2022
DOI: 10.15311/selcukdentj.1187225
|View full text |Cite
|
Sign up to set email alerts
|

Nazopalatin Kanal Morfolojisinin Konik Işınlı Bilgisayarlı Tomografi Kullanılarak Değerlendirilmesi

Abstract: Amaç: Nazopalatin kanalın (NPK) farklı morfolojik tipleri bulunmaktadır. Bu çalışmanın amacı; NPK morfolojisinin konik ışınlı bilgisayarlı tomografi (KIBT) görüntüleri üzerinden morfolojik olarak değerlendirmektir. Gereç ve Yöntemler: Rastgele seçilen 500 hastanın KIBT görüntüleri retrospektif olarak taranmıştır. Sagittal kesit üzerinde yapılan incelemede hastaların yaş ve cinsiyetlerine göre NPK morfolojik tipleri (silindirik, ağaç dalı, kum saati, huni, muz ve konik) incelenmiştir. Bulgular: Bu ç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Han et al (7),. Naitoh et al(14), Yeşiltepe et al(17), Yalçın and Akyol(8) categorizations allow comparison with each other and with the TCC definition in our study. The TCC frequency we found is less than the TCC frequency observed in Yeşiltepe et al(17) in study, and is higher than the frequency in the studies of Han et al(7), Naitoh et al(14), Yalçın and Akyol(8).…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…Han et al (7),. Naitoh et al(14), Yeşiltepe et al(17), Yalçın and Akyol(8) categorizations allow comparison with each other and with the TCC definition in our study. The TCC frequency we found is less than the TCC frequency observed in Yeşiltepe et al(17) in study, and is higher than the frequency in the studies of Han et al(7), Naitoh et al(14), Yalçın and Akyol(8).…”
mentioning
confidence: 73%
“…Naitoh et al(14), Yeşiltepe et al(17), Yalçın and Akyol(8) categorizations allow comparison with each other and with the TCC definition in our study. The TCC frequency we found is less than the TCC frequency observed in Yeşiltepe et al(17) in study, and is higher than the frequency in the studies of Han et al(7), Naitoh et al(14), Yalçın and Akyol(8). As Han et al(7), Yalçın and Akyol (8) found the frequency of TCC to be higher in men, as in our study, Naitoh et al(14) and Ye-Type 4 canal comply with the TCC definition of this study.…”
mentioning
confidence: 73%
See 2 more Smart Citations